Applying Aristotelian Ethics to Combat Corruption in Indonesia: Virtue, Moral Education, and Ethical Governance - Maximilian Amenangi Sadali Nitisara Wawo Runtu; I Gede Saman (Jurnal Riset Rumpun Agama dan Filsafat, 2026)
Corruption remains a persistent challenge in Indonesia because it weakens public trust, undermines welfare, and obstructs equitable development. This article examines how Aristotle’s virtue ethics can contribute to anti-corruption efforts by addressing the moral roots of corrupt behavior. The study argues that corruption is not only a legal or administrative violation but also a failure of character, judgment, and commitment to the common good. Using a qualitative conceptual design, the article employs philosophical analysis, a structured literature review, and Socratic questioning to examine the relationship between virtue, leadership, and public integrity. The analysis identifies three principal roots of corruption: weak moral character, poor ethical judgment, and self-interest over the common good. It shows that Aristotelian ethics offers an integrated response through the cultivation of moral virtue, intellectual virtue, and practical wisdom. The findings suggest that virtue-based ethics is most effective when combined with anti-corruption education, ethical leadership, stronger rule-of-law implementation, and institutional arrangements that reduce opportunities for abuse of power. Aristotle’s framework does not provide a complete solution, but it offers a valuable normative foundation for strengthening ethical public culture in Indonesia.